Punctuations used by Filipino and Thai students in their essays: A corpus-based inquiry - Jaezzir Mae Arquiola; Esperval Cezhar Cadiao; Christian Roy Leyga; Ronnel Sarsuelo (Journal of English Language and Pedagogy, 2022)
Writing, being one of the most vital skills to develop, is of great importance. It is imperative that one needs to master not just the structure but also the functions of punctuation marks. It is undeniable that punctuation marks seem confusing and are used interchangeably among Thai and Filipino students. Consequently, the written output of the students becomes incomprehensible due to the misuse or the absence of punctuation. This study aimed to determine the average common errors of Filipino (ESL) students and Thai (EFL) students when it comes to using punctuation marks in writing essays and to find out the significant difference. The researchers also pointed out the possible causes of why Thai and Filipino students committed such errors. To further illustrate the results of the study, the researchers opted to present the errors individually through tables and charts and interpreted the figure based on the total percentage of individual respondents, and eventually identified the committed error as a whole. There were 30 participants in the research composed of 15 Thai (EFL) students and 15 Filipino (ESL) students. The sources of data were the written essays of the 30 participants. The total percentage was used to treat the data to identify the average punctuation errors committed by the participants and the significant difference in the committed errors between the Thai EFL and Filipino ESL learners. The result showed a significant difference in the punctuation errors committed between Thai and Filipino students with a comma (,) receiving the largest number of errors.